Direct International Comparison of EU Member States Fiscal Decentralization Systems with the Conceptual Index of Fiscal Decentralization (CIFD) in the Context of European Charter of Local Self-Government (ECLSG) - Mateja Finžgar; Boštjan Brezovnik (Transylvanian Review of Administrative Sciences, 2019)
The paper presents a direct international comparison of the existing fiscal decentralization systems of European Union member states (hereinafter EU-28), which are also signatories of the European Charter of Local Self-Government (hereinafter ECLSG or Charter). The results of the benchmarking show that the conceptual index of fiscal decentralization (hereinafter CIFD) is an appropriate tool for direct international comparison of different fiscal decentralization systems, while allowing measurements of their effectiveness, as there is a direct link between the CIFD and the basic principles of the ECLSG. The CIFD is an upgrade of classical methods (indicators) used to measure fiscal decentralization, and, at the same time, reflects the consideration of the selected basic principles of the ECLSG. The CIFD consists of five indicators, four of which represent quantified selected basic principles of the ECLSG, and the fifth indicator represents the number of lower management levels. Thus, with the use of CIFD, the EU-28 obtained definite levels of fiscal decentralization, while, due to the established direct link between the CIFD and the ECLSG guidelines, the indices in the index structure themselves indicated either greater or lesser compliance of their fiscal decentralization systems with the selected basic principles of the Charter. The paper concludes with a simulation of an empirical conceptual model of fiscal decentralization (hereinafter CMFD) which is now offering the opportunity to identify critical points or shortcomings of the existing fiscal decentralization system in each country, limiting or even eliminating them with the aim of achieving a highly efficient system of fiscal decentralization.